Beziehungspflege im Wettbewerb Der Deutsche Orden im 14. Jahrhundert - Paravicini, Werner (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2020)
Caring for good relations. The Teutonic Order in competition during the 14th century This paper does not concentrate on the period of open competition with Poland-Lithuania from 1386/1387 onward, but on the time before, quite less well known, though one example will be posterior. Anterior to about 1390 the documention is scarce. But a single document can shed light on a general practice, thus the report on the 1375 expedition sent to the General Proctor of the Order present in Rome. He was the only permanent informant about the activity of the Order at a princely court. But there were other persons which, from time to time, had similar functions: The economic representative at Bruges and his superiors, the Great Proctors of Marienburg and Königsberg, and the herald of the Order. We see all of them go to Western Europe, where they brought and received gifts from and to the Great Master, who participated fully in the gift-exchange between courts. Naturally there were also occasional diplomatic missions. One of them is particularily well documented, on both sides, since the reports of Dietrich von Logendorf in 1409 are still extant. Since gifts had to be precious or at least rare, the Great Master was in a good position: He could offer amber and prussian-lituanian-polish specialities, and falcons, the gift of which he developped into a permanent system of European renown, exceptionally well documented. Relatively rare was the gift of the familiarity of the Order, but there is a lack of archival tradition. Finally, the Table of Honour, celebrated in the context of the Lithuanian expeditions was quite an attraction. Its history, not yet completely elucidated, takes us back to 1375 and poses the question of the origins, of the Table itself and of the practice of its announcements. In general, the care itself is not a warrantee for good relations. It was obliged, without assuring positive results. What it was good for gets visible only when one refused to participate in this valse of politeness, attention and good will: He declares himself an ennemy.